Static Output Feedback Control for Discrete-Time Switched Systems via Improved Path-Following Method - Jian Chen; Chong Lin (Discrete Dynamics in Nature and Society)
This paper focuses on the problems of static output feedback control and H∞ controller design for discrete-time switched systems. Based on piecewise quadratic Lyapunov functions and a new linearization method, new sufficient conditions for system stability and H∞ controller design are obtained. Then, an improved path-following algorithm is built to solve the problems. Finally, the merits and effectiveness of the proposed method are shown by two numerical examples.